Light penetration ability assessment of satellite band for seagrass detection using landsat 8 OLI satellite data - Misbari, S. (Springer Verlag, 2016)
Seagrass distribution is controlled by light availability, especially at the deepest edge of the meadow. Light attenuation due to both natural and anthropogenically-driven processes leads to reduced photosynthesis. Reliability of satellite-based seagrass mapping under different water clarity that has different attenuation coefficient value is still not fully known. Understanding the minimum light requirements for growth is crucial when light conditions are insufficient to maintain a positive carbon balance, leading to a decline in seagrass growth and distribution. By comparing the seagrass-detected pixels at two different coastal locations with the corresponding depth from the nautical chart, the assessment of seagrass map derived from Landsat 8 OLI satellite data were performed. We presented the assessment of light penetration capability of Landsat 8 OLI bands in typical tropical coastal water of Malaysia, with special attention on the different water clarity that has different amount of light deprivation on the seagrass meadow.